Detection of electrically neutral and nonpolar molecules in ionic solutions using silicon nanowires. (22nd March 2017) - Wu, Ying-Pin; Chu, Chia-Jung; Tsai, Li-Chu; Su, Ya-Wen; Chen, Pei-Hua; Moodley, Mathew K; Huang, Ding; Chen, Yit-Tsong; Yang, Ying-Jay; Chen, Chii-Dong
Abstract: We report on a technique that can extend the use of nanowire sensors to the detection of interactions involving nonpolar and neutral molecules in an ionic solution environment. This technique makes use of the fact that molecular interactions result in a change in the permittivity of the molecules involved. For the interactions taking place at the surface of nanowires, this permittivity change can be determined from the analysis of the measured complex impedance of the nanowire. To demonstrate this technique, histidine was detected using different charge polarities controlled by the pH value of the solution. This included the detection of electrically neutral histidine at a sensitivity of 1 pM. Furthermore, it is shown that nonpolar molecules, such as hexane, can also be detected. The technique is applicable to the use of nanowires with and without a surface-insulating oxide. We show that information about the changes in amplitude and the phase of the complex impedance reveals the fundamental characteristics of the molecular interactions, including the molecular field and the permittivity.